Perkembangan Model Data Temporal serta Implementasinya pada Database Management Systems - Supria Supria (Bina Nusantara University, 2023)
This essay examines how temporal data models are created and how they are integrated into database management systems. The well-known Relational Data Model’s extension, the Temporal Relational Data Model, is discussed. The application of this temporal data model in database management systems is also researched. The Historical Relational Data Model adds timestamps to attributes, and the Temporal Relational Model adds timestamps to tuples. These two approaches make up the temporal data model. It has become apparent via the implementation of this temporal data model that not all temporal data ideas are applicable to database management systems. IBM DB2 has explicitly integrated the idea of time stamps, but not the idea of PERIOD data type. While Teradata has implemented the PERIOD data type, but has not yet implemented the concept of explicit timestamps.